The vitamin D receptor functional variant rs2228570 (C>T) does not associate with type 2 diabetes mellitus. (2nd October 2017) - Bertoccini, Laura; Sentinelli, Federica; Leonetti, Frida; Bailetti, Diego; Capoccia, Danila; Cimini, Flavia A.; Barchetta, Ilaria; Incani, Michela; Lenzi, Andrea; Cossu, Efisio; Cavallo, M. Gisella; Baroni, Marco G.
ABSTRACT: Aim : Vitamin D acts through the binding to the vitamin D receptor (VDR). Several polymorphisms in VDR gene have been studied. Among these, the rs2228570 C>T (FokI) variant has been demonstrated to be functional, leading to a protein with a different size and activity. So far, genetic studies on the association between VDR gene rs2228570 single nucleotide polymorphism (SNP) and type 2 diabetes mellitus (T2DM) showed contradictory results. Thus, we performed an association study in a large cohort of adult Italian subjects with T2DM and in nondiabetic controls.Materials and methods : For this study, 1713 subjects, 883 T2DM patients and 830 controls, were genotyped for the polymorphism. All participants without a diagnosis of diabetes underwent oral glucose tolerance test (OGTT), with measurement of glucose and insulin levels. Indices of insulin resistance (Homeostatic model assessment of insulin resistance, insulin sensitivity index), secretion (homeostatic model assessment for beta-cell, corrected insulin response at 30 minutes) and disposition index were calculated.Results : Genotype distributions and allele frequencies did not show difference between T2DM subjects and controls. We did not find significant differences among the three genotypes regarding gender, age, BMI, waist, hip, waist-to-hip ratio, and blood pressure. There were also no significant differences in lipid parameters, aspartate aminotransferase, and alanine aminotransferase levels. We tested for association with OGTT-derived data and surrogate indices of insulin resistance and secretion. We did not find significant differences among the genotypes in any of above-mentioned parameters. Furthermore, vitamin D levels were measured in a subgroup of subjects. We did not find significant differences among the genotypes.Conclusions : Our study does not provide evidence for the association of the rs2228570 polymorphism with T2DM in a Caucasian population.